Pengetahuan, Keterburuan, dan Produktivitas: Analisis Komparatif Amsal 19:2 dan Hukum Hasil yang Menurun David Ricardo - Jansen Hutabarat; Selamat Siregar (Universitas Methodist Indonesia, 2026)
This interdisciplinary study investigates the intersection of biblical wisdom and classical economic theory by analyzing Proverbs 19:2 in dialogue with David Ricardo’s Law of Diminishing Returns. Proverbs 19:2 underscores the primacy of da‘at (knowledge or practical wisdom) as a guiding principle, cautioning against impulsivity and haste, which lead to errors, inefficiencies, and resource mismanagement. Correspondingly, Ricardo’s law demonstrates that the unregulated addition of inputs results in diminishing marginal productivity, highlighting the necessity of strategic balance in resource allocation. Drawing on liberal Christian theological perspectives, Jewish wisdom scholarship, and economic theory, this research elucidates the functional equivalence between ethical prudence and productivity optimization. Findings indicate that wisdom operates both as a moral regulator and as a practical instrument for enhancing organizational and personal efficiency. The study further explores implications for contemporary work ethics, time management, and the conceptualization of labor as a vocation (vocatio) rather than a mere input-output process. By bridging theological reflection and economic reasoning, this research contributes to the emerging field of theology-economics, offering a framework wherein ethical discernment and strategic action converge to promote sustainable productivity and holistic human flourishing.